2022
DOI: 10.1101/2022.07.26.22278002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection is associated with anti-desmoglein 2 autoantibody detection

Abstract: Post-acute cardiac sequelae, following SARS-CoV-2 infection, are well recognised as complications of COVID-19. We have previously shown the persistence of autoantibodies against antigens in skin, muscle, and heart in individuals following severe COVID-19; the most common staining on skin tissue displayed an inter-cellular cement pattern consistent with antibodies against desmosomal proteins. Desmosomes play a critical role in maintaining the structural integrity of tissues. For this reason, we analysed desmoso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In addition, autoantibodies to IL-1RA were also present in 62% (13/21) of samples of multisystem inflammatory syndrome in children (MIS-C), and further research is required to see if these have pathological effects [ 418 ]. Other studies awaiting peer-review notably observed significant increases in autoantibodies (n = 30) in severity to desmoglein 2 (DSG2), that can be present in heart, skin, or skeletal muscle [ 419 ]. The significance of autoantibody changes, presently, is largely unclear in research, and other authors concur that this could be a transient change but would need further research [ 420 ].…”
Section: Autoantibodies In Sars-cov-2 Researchmentioning
confidence: 99%
“…In addition, autoantibodies to IL-1RA were also present in 62% (13/21) of samples of multisystem inflammatory syndrome in children (MIS-C), and further research is required to see if these have pathological effects [ 418 ]. Other studies awaiting peer-review notably observed significant increases in autoantibodies (n = 30) in severity to desmoglein 2 (DSG2), that can be present in heart, skin, or skeletal muscle [ 419 ]. The significance of autoantibody changes, presently, is largely unclear in research, and other authors concur that this could be a transient change but would need further research [ 420 ].…”
Section: Autoantibodies In Sars-cov-2 Researchmentioning
confidence: 99%
“…This raises the possibility that autoimmunity could contribute to the development of acute and chronic symptoms of COVID-19. DSG2 autoantibodies have the potential to be pathogenic and have been associated with ARVC and familial DCM [ (47,12]. In addition, the presence of DSG2 autoantibodies has been demonstrated to disrupt the normal functioning of DSG2 proteins, leading to interference with cell-to-cell adhesion [66,67].…”
Section: Association Between Dsg2 Expression and Severity Of Covid-19...mentioning
confidence: 99%
“…Moreover, DSG2 and its autoantibody have both been implicated in the pathogenesis of many diseases especially those involving cardiac injury [66,103,104]. This recently includes COVID-19 [12,47].…”
Section: Dsg2 and Dsg2 Autoantibodies As Biomarkers For Covid-19 Infe...mentioning
confidence: 99%
See 2 more Smart Citations